A preliminary study on form 1 students’ errors and misconception in operations of integers - Khalid, Madihah; Othman, Joharry; Ibrahim, Mohd Burhan; Embong, Zulmaryan (Universiti Sultan Zainal Abidin, 2018)
Students have difficulty in understanding various topics of Mathematics because many of them usually depend on rote memorization of the material that they have learned. This include the mo st basic area of numbers and operations, such as 'operations on integers'. In solving problems involving integers, students usually apply rules that they blindly memorize due to poor conceptual understanding of the topic. This in turn leads to difficulty in applying basic knowledge especially in solving algebraic equations as they progress. The main purpose of this paper is to validate and present the preliminary findings of a paper and pencil test used to diagnose the errors exhibited by Form 1 students in West Malaysia. The errors is then categorized into categories that were documented by other studies from the literature review and unique findings from the Malaysian students. A stratified sample of 622 students from eight different schools (urban and rural), representing four different regions of West Malaysia (North, South East and Middle) were involved in this study. Students were given a diagnostic test consisting of 40 routine problems in operations of integers to uncover the errors and misconception held by some of them. SPSS was used to analyse the data. The result shows that the diagnostic test is a reliable and valid instrument for detection of students’ errors and misconception in operations involving integers. The results also show that despite the simple routine problems, errors and misconceptions were evidently committed by more than 50% the students in certain categories of the test. Most of the errors that students commit involve the ‘addition’ and ‘subtraction’ operation on mixed positive and negative numbers, due to various misunderstanding, or misconception as well as getting confused with the rules being taught in class